2022
DOI: 10.1088/1674-1056/ac4a6c
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of identification methods of key nodes in transportation network

Abstract: The identification of key nodes plays an important role in improving the robustness of the transportation network. For different types of transportation networks, the effect of the same identification method may be different. It is of practical significance to study the key nodes identification methods corresponding to various types of transportation networks. Based on the knowledge of complex networks, the metro networks and the bus networks are selected as the objects, and the key nodes are identified by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Network attack is a commonly used method to verify the accuracy of evaluation results [43,44]. With the ranks of nodes, the attack order can be obtained.…”
Section: Verification Of Identification Resultsmentioning
confidence: 99%
“…Network attack is a commonly used method to verify the accuracy of evaluation results [43,44]. With the ranks of nodes, the attack order can be obtained.…”
Section: Verification Of Identification Resultsmentioning
confidence: 99%
“…It is concluded that different node importance evaluation indicators have different effects on the rail network performance. Some scholars try to apply and compare the existing complex network importance evaluation methods to the URTNs [35,36]. Lai et al [36] established urban rail topology models of multiple cities, the toke network efficiency, and the largest connected subgraph as indicators to measure the network performance, and they found that the KSD identification method was superior to the node degree, neighbor node degree, DKS, and DKSN identification methods.…”
Section: Evaluation Of Node Importance Of Urban Rail Networkmentioning
confidence: 99%
“…Some scholars try to apply and compare the existing complex network importance evaluation methods to the URTNs [35,36]. Lai et al [36] established urban rail topology models of multiple cities, the toke network efficiency, and the largest connected subgraph as indicators to measure the network performance, and they found that the KSD identification method was superior to the node degree, neighbor node degree, DKS, and DKSN identification methods. Some scholars realized that there are differences in node importance in different application environments, and they tried to improve and even build new evaluation methods to more accurately obtain the key nodes that have the greatest impact on the urban rail network performance [37][38][39].…”
Section: Evaluation Of Node Importance Of Urban Rail Networkmentioning
confidence: 99%
“…Connectivity theory in Indonesia may be used to road conditions in the region, as it is used to achieve good outcomes in the manufacturing and use of transportation in Indonesia subsequently. Connection theory is used to analyze connectivity in a region by understanding the character of the place in terms of its people's modernity, the smoothness of current traffic and transportation, and the smooth operation of the local economy [30]. The real state of connectivity in the field, can help plan and build infrastructure and as well as further facilities that support the implementation of regional development in the region concerned.…”
Section: Connectivitymentioning
confidence: 99%